The transcriptional analysis of pepper shed light on a proviral role of light-harvesting chlorophyll a/b binding protein 13 during infection of pepper mild mottle virus - Lin, Weihong; Zhang, Shugen; Zhang, Hao; Deng, Xiaomei; Jiang, Tong; Chen, Xifeng; Dong, Laihua; Yan, Qin; Zang, Lianyi; Xing, Yongping; Wang, Zhenquan; Zhang, Qin; et al. (Frontiers in Plant Science, 2025)
Pepper mild mottle virus (PMMoV), a member of the genus Tobamovirus, causes severe damage on pepper worldwide. Despite its impact, the pathogenicity mechanisms of PMMoV and the pepper plant’s response to infection remain poorly understood. Here, we compared the transcriptomic changes in a susceptible pepper inbred line 21C241 with a resistant inbred line 21C385 seedlings, following systemic PMMoV infection using RNA sequencing. Our results revealed that PMMoV induced more pronounced mosaic symptoms and higher viral accumulation levels in the susceptible line 21C241 compared to the resistant line 21C385. We identified 462 and 401 differentially expressed genes (DEGs) in the systemically-infected leaves of the susceptible and resistant lines, respectively, when compared to their healthy counterparts. The majority of these DEGs were involved in photosynthesis and the biosynthesis of secondary metabolites, with 28 DEGs exhibiting distinct expression patterns between the two lines. Notably, the expression level of the chlorophyll a-b binding protein 13 (CAB13) was significantly up-regulated in resistant line 21C385 following PMMoV infection. Functional analysis through silencing of CAB13 in pepper and Nicotiana benthamiana demonstrated a reduction in PMMoV accumulation, suggesting that CAB13 plays a positive role in facilitating PMMoV infection in pepper plants. Taken together, our findings highlight the distinct gene expression profiles between susceptible and resistant pepper lines in response to PMMoV infection and confirm the proviral role of CAB13. This study provides valuable insights into the molecular mechanisms underlying resistance and susceptibility in pepper plants and may inform future strategies for disease management.